Fabrication of conjugated triblock copolymer/single-walled carbon nanotubes composite films with enhanced thermoelectric performance. (October 2021) - Zhang, Yunfei; Chen, Siying; Zhang, Hui; Ding, Xinyue; Fu, Ping; Du, Feipeng
Abstract: Aniline tetramer-b-polyethylene glycol-b-aniline tetramer (APA), a kind of conjugated triblock copolymer, has attracted attention in the thermoelectric (TE) conversion field owing to its typical n-type property, well-deﬁned molecular structure and excellent dissolvability. Here, APA is used as n-type dopant for tuning the TE properties of the single-walled carbon nanotubes (SWCNTs), and APA/SWCNT TE composites are fabricated by a facile solution mixing method. Scanning electronic microscopy and transmission electron microscope, X-ray photoelectron spectroscopy, X-ray diﬀraction, Raman spectroscopy, UV–Vis spectroscopy and thermogravimetric analysis are utilized to elucidate the morphology, elemental composition, structure and thermal stability of the composites, respectively. For one thing, APA provides enough negative charge at high temperature to convert the SWCNTs into n-type material, and a maximum Seebeck coefficient of −49.0 ± 0.3 μV/K at 125 °C for APA/SWCNT (40:100) was obtained. For another thing, HCl doping further improves the TE properties of APA/SWCNT, and the highest power factor of 106.3 μW/(m·K 2 ) is obtained at 100 °C for APA/SWCNT (10:100). Therefore, this work provides a facile method using a new dopant APA to fabricate n-type APA/SWCNT composite with enhanced thermoelectric performance. Highlights: Aniline tetramer-b-polyethylene glycol-b-aniline tetramer (APA)/SWCNT thermoelectric composites are prepared. APA works as n-type dopant for tuning the TE properties of APA/SWCNT. APA/SWCNT composite shows temperature sensitivity. HCl doping further improved the TE properties of APA/SWCNT.